2013
DOI: 10.1212/wnl.0b013e318281ccec
|View full text |Cite
|
Sign up to set email alerts
|

Whole-brain magnetic resonance spectroscopic imaging measures are related to disability in ALS

Abstract: Objective: To demonstrate the sensitivity of a recently developed whole-brain magnetic resonance spectroscopic imaging (MRSI) sequence to cerebral pathology and disability in amyotrophic lateral sclerosis (ALS), and compare with measures derived from diffusion tensor imaging.Methods: Whole-brain MRSI and diffusion tensor imaging were undertaken in 13 patients and 14 agesimilar healthy controls. Mean N-acetylaspartate (NAA), fractional anisotropy, and mean diffusivity were extracted from the corticospinal tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…Other studies [10] have reported that FA and NAA within the entire white matter are significantly decreased in ALS patients compared with controls, and our results are in accordance with the decrease in the FA or NAA/Cr for each side. However, we failed to show a significant change in the NAA on either side.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Other studies [10] have reported that FA and NAA within the entire white matter are significantly decreased in ALS patients compared with controls, and our results are in accordance with the decrease in the FA or NAA/Cr for each side. However, we failed to show a significant change in the NAA on either side.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, advanced MRI measurements are needed to explore ALS, including whole-brain magnetic resonance spectroscopic imaging (MRSI) [10]. ALS could be better understood if the research community developed a perfect ALS animal model.…”
Section: Discussionmentioning
confidence: 99%
“…In a well-received recent paper [14] and Editorial [15,16], Neurology applauded this study which yielded unique information about NAA distribution along motor tracts in patients with ALS, which was superior in reflecting motor defects than the previously much-lauded DTI --tractography. What is wrong with this approach?…”
Section: Solutions Used By Other 'Quantitative' Modalities Are Availamentioning
confidence: 99%
“…The combination of NAA and myo-inositol may improve the specificity of the test, but further studies are needed [164]. Using whole-brain resonance spectroscopic imaging, NAA levels are significantly associated with a degree of disability [165]. Recent advances in proton magnetic resonance spectroscopy ( 1 H-MRS) allow for the direct quantification of GABA (gamma-aminobutyric acid) in the cortex [166].…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%